PENGARUH DIVERSIFIKASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN ( Studi pada Toko Greatman Distro Krunggeukueh ) - Cut Yusnidar; Nanda Ameliany (Program Studi Administrasi Bisnis, 2023)
This research was conducted at the Greatman Krunggeukueh Shop, where there was an increase and decrease in the number of customers in January-December 2022. In January the number of sales reached 49 products, then in February it reached 69 products. Then the author conducted an initial survey on 30 customers of the Greatman Krunggeukueh distro shop, where 45% of customers stated that the products at the Greatman distro shop did not have a new appeal. Therefore, this research aims to see how product diversification influences purchasing decisions at the Greatman Krunggeukueh Distro Store. Indicators of product diversification in this research consist of product attractiveness, product suitability, customer trust in the product, customer impression of the product, attractiveness of the product packaging process, suitability of the product packaging process and offering gift stickers at the time of purchase. Meanwhile, purchasing decision indicators in this research consist of product selection, brand selection, supplier selection, time and number of purchases. This research used quantitative research using a purposive sampling approach, obtaining 96 respondents as the research sample. Data analysis used in this research used the SPSS 25.0 software program. Based on the research results, it shows that the product diversification variable partially has a positive and significant effect on purchasing decisions with a product diversification variable value of 16.033 < 1.986 and a significant value of 0.000 > 0.05